Cytotoxic Effect of Methanolic Extract of Terminalia chebula Retz Fruit on the Leishmania Major In vitro - H Noormohammadi; Y Maroufi; M Dabirzadeh; AH Miri; A Geraili (Institue of Medicinal Plants, ACECR, 2016)
Background: Cutaneous leishmaniasis is one of major public health problem in many countries. Pentavalent antimonite components as first line treatment of cutaneous leishmaniasis has many limitations and side effects. Objective: The aim of this study was to investigatethe cytotoxic effect of methanolic extract of Terminalia chebula Retz fruit on the Leishmania major in vitro. Methods: Terminalia chebula Retz fruit extract with 80, 125, 250 and 500 µg/ml concentrations with leishmania promastigotes were added to 96-well plate as 4-time repeated and incubated in 21 ˚C. Viability percent of promastigotes was estimated by direct counting and MTT assay; after 24, 48 and 72 hours. Terminalia chebula Retz extract with80 and 250 μg/ml were added to infected macrophages. The mean of amastigotes in each macrophage was obtained after 24 and 48 hours. Statistical analysis of data was done by SPSS software and one-way ANOVA test. Results: viability percent of promastigotes in groups treated by maximum and minimum concentrations (500 and 80 μg/ml) of Terminalia chebula Retz after 24 hours was 19.01% and 98.65%, respectively.Viability of this groups after 48hours was 7.81% and 97.26% and after 72 hours it was 31.61% and 97.26%, respectively. IC50 for 24 hours was 114.10 µg/ml. Cytotoxicity of Terminalia chebula Retz extract (80 and 250 μg/ml) in amastigotes after 24 hours was 40.35% and 29.99%; and after 48 hours was 45.21% and 41.11%, respectively. Conclusion: extract of Terminalia chebula Retz fruit has cytotoxic effect on the promastigotes and amastigotes of L. major in vitro.